EVALUATING THE SUCCESS OF PEACE OPERATIONS - Garb, Maja (Scientia Militaria - South African Journal of Military Studies, 2014)
Questioning and investigating the success of peace operations is not a new research activity. However, there are still many open questions, because the surveys do not show the same results. One of the crucial points in the analysis of the success of peace operations is a definition of such success. In this article, firstly, several debates on success evaluation, previously published definitions and criteria of success are explored, and some survey results are presented. Secondly, the evaluations of success of almost all peace operations made by students of International Relations and Defence Studies at the Faculty of Social Sciences in the study year 2008/2009 are presented and analysed. The success criteria used by the students in their evaluations comprise the main research question of the article. The analysis showed that three criteria were mostly used, namely fulfilment of the mandate or goals, the political and security situation, and assistance to the local population.